2020
DOI: 10.3390/s20175000
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Sensor Approach Based on an Echo State Network Optimized by Improved Genetic Algorithm

Abstract: In the process of fault diagnosis and the health and safety operation evaluation of modern industrial processes, it is crucial to measure important state variables, which cannot be directly detected due to limitations of economy, technology, environment and space. Therefore, this paper proposes a data-driven soft sensor approach based on an echo state network (ESN) optimized by an improved genetic algorithm (IGA). Firstly, with an ESN, a data-driven model (DDM) between secondary variables and dominant variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, genetic algorithm (GA) was able to improve the performance of models with fewer input factors [59,60]. In northern Greece, it was found that ANN models with fewer inputs gave rise to lower accuracy than the GA optimized ANN model [61]. In South Korea, it was reported that GABP models estimated daily ET 0 with acceptable accuracy using only temperature data [29].…”
Section: Genetic Algorithm Improves the Performance Of Modelsmentioning
confidence: 99%
“…However, genetic algorithm (GA) was able to improve the performance of models with fewer input factors [59,60]. In northern Greece, it was found that ANN models with fewer inputs gave rise to lower accuracy than the GA optimized ANN model [61]. In South Korea, it was reported that GABP models estimated daily ET 0 with acceptable accuracy using only temperature data [29].…”
Section: Genetic Algorithm Improves the Performance Of Modelsmentioning
confidence: 99%
“…and by the output computed as: ) defines the extended reservoir state, and a bias term, respectively. A key issue for ESN is to determine W out utilizing the known samples [156]. The ESN's low computational complexity and its ability to capture the process data's dynamic relationships (due to the reservoir's self-and feedback connections and a sparse connection weight matrix) makes it ideal for real-time monitoring, fault detection (important for data quality assurance), and monitoring the reliability of the model predictions [139,141].…”
Section: Echo State Network (Esns)mentioning
confidence: 99%
“…In [73], an improved GA was proposed with the immigration strategy. In [74], authors proposed a multi-step learning method for optimizing the hyper-parameters of multiple reservoirs ESNs.…”
Section: Optimization Of Hyper-parametersmentioning
confidence: 99%